2018
DOI: 10.3899/jrheum.180615
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Nailfold Capillaroscopy Is Common in Patients with Connective Tissue Disease and Associated with Abnormal Pulmonary Function Tests

Abstract: Objective.To assess the presence of a systemic sclerosis (SSc) pattern on nailfold capillary microscopy (NCM) in patients with Raynaud phenomenon (RP) and to explore its association with abnormal pulmonary function tests (PFT).Methods.NCM patterns were assessed in 759 consecutive patients with RP. Patterns were classified as normal (n = 354), nonspecific (n = 159), or SSc pattern (n = 246). Abnormal PFT was defined as forced vital or diffusion capacity < 70%. Patients were classified as primary RP (n = 245)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 38 publications
2
35
0
1
Order By: Relevance
“…We thank Dr. Lambova for her interesting comment 1 on our recent article published in The Journal 2 . We reported that a systemic sclerosis (SSc) or scleroderma-like capillaroscopic pattern is common in patients with Raynaud phenomenon, and can be frequently observed in patients with connective tissue diseases (CTD) other than SSc.…”
Section: Dr Van Roon Et Al Replymentioning
confidence: 97%
“…We thank Dr. Lambova for her interesting comment 1 on our recent article published in The Journal 2 . We reported that a systemic sclerosis (SSc) or scleroderma-like capillaroscopic pattern is common in patients with Raynaud phenomenon, and can be frequently observed in patients with connective tissue diseases (CTD) other than SSc.…”
Section: Dr Van Roon Et Al Replymentioning
confidence: 97%
“…The recently published paper by van Roon, et al addresses an interesting question about the presence of "scleroderma" pattern in different connective tissue diseases and its association with abnormal pulmonary function tests 1 . The authors have detected it in 88% of cases with systemic sclerosis (SSc; 35/40), in 17% of patients with systemic lupus erythematosus (SLE; 5/30) and in 13% of patients with rheumatoid arthritis (RA; 2/15).…”
Section: Scleroderma-like Pattern In Various Rheumatic Diseasesmentioning
confidence: 99%
“…It appears early in the disease course, facilitates early diagnosis, and is accepted as a diagnostic criterion. Scleroderma-like pattern could be observed in a smaller proportion of patients with other rheumatic diseases (i.e., SLE, RA, and others) [1][2][3][4][5][6][7][8][9] .…”
Section: Scleroderma-like Pattern In Various Rheumatic Diseasesmentioning
confidence: 99%
“…In this issue of The Journal, Van Roon, et al assessed the presence of an SSc pattern on nailfold capillaroscopy in consecutive patients with RP at the tertiary referral center, Department of Internal Medicine, University Medical Center Groningen, the Netherlands, and examined its association with pulmonary function tests 2 years or more after presentation 17 . There were 759 patients with RP classified as having primary RP (n = 245) when their serology was negative and when they had a "normal" nailfold capillaroscopy and no clinical symptoms of CTD during followup (2 years or more following presentation), or otherwise as secondary RP (n = 514).…”
mentioning
confidence: 99%
“…Van Roon, et al had the ambitious aim of assessing capillaroscopy as "proxy" for lung involvement in CTD 17 . The results of their study show that there are signals that both SSc pattern and CTD antibodies are supportive aids in managing patients with CTD.…”
mentioning
confidence: 99%